Characterization of tetraethylammonium uptake across the basolateral membrane of the Drosophila Malpighian (renal) tubule. - Rheault, M.R.; Debicki, D.M.; O'Donnell, M.J. (American Journal of Physiology, 2005)
Basolateral transport of the prototypical type I organic cation tetraethylammonium (TEA) by the Malpighian tubules of Drosophila melanogaster was studied using measurements of basolateral membrane potential (V(bl)) and uptake of [(14)C]-labeled TEA. TEA uptake was metabolically dependent and saturable (maximal rate of mediated TEA uptake by all potential transport processes, reflecting the total transport capacity of the membrane, 0.87 pmol.tubule(-1).min(-1); concentration of TEA at 0.5 of the maximal rate of TEA uptake value, 24 muM). TEA uptake in Malpighian tubules was inhibited by a number of type I (e.g., cimetidine, quinine, and TEA) and type II (e.g., verapamil) organic cations and was dependent on V(bl). TEA uptake was reduced in response to conditions that depolarized V(bl) (high-K(+) saline, Na(+)-free saline, NaCN) and increased in conditions that hyperpolarized V(bl) (low-K(+) saline). Addition of TEA to the saline bathing Malpighian tubules rapidly depolarized the V(bl), indicating that TEA uptake was electrogenic. Blockade of K(+) channels with Ba(2+) did not block effects of TEA on V(bl) or TEA uptake indicating that TEA uptake does not occur through K(+) channels. This is the first study to provide physiological evidence for an electrogenic carrier-mediated basolateral organic cation transport mechanism in insect Malpighian tubules. Our results also suggest that the mechanism of basolateral TEA uptake by Malpighian tubules is distinct from that found in vertebrate renal tubules.